(untitled) (Journal of Economic Research & Business Administration, 2015)
Modern conditions of economic development and cardinal changes of tendencies of the market of food products cause need of creation of new approaches to management of the food enterprises for their survival and development during crisis. During this period such activities of the enterprise, as the analysis of the market and competitors, statement of strategic objectives, marketing support of goods, innovative activity, search and optimization of investment resources, activity planning in long-term prospect taking into account future changes of the market, development of scenarios of development are of particular importance. For the analysis we chose brewing branch of the food industry as most dynamically developing. Our choice was defined also by existence of the large international and national companies in the beer market of Kazakhstan, and also high level of the competition that causes as a whole need of high level of strategic management of brands.